Business Prospect of Recycling Household Wastage: A Study on Gopalganj District of Bangladesh - Hossain, Md. Solaiman; Islam, Md. Saiful; Prova, Atia Ibnat; Saha, Monisha; Neogy, Taposh Kumar (Global Disclosure of Economics and Business, 2022)
To find out the business prospect of recycling household wastage in Gopalganj districts the main target of this research. To conduct this research the authors have collected the data from both primary and secondary sources. Mainly, interview and observation methods have been used to collect primary data and various types of published and unpublished documents, websites, etc. have been used to collect secondary data. From this study, it has been found that there is a potential business prospect of recycling the household wastage and it will contribute significantly to increasing the land productivity and reducing the unemployment problem of Gopalganj district. If it is possible to implement this research idea, it will increase business opportunities and save the environment from pollution. To conduct this research it was very difficult for the authors to collect the data by physically observing the dumping sites.